Chronic NOS inhibition accelerates NAFLD progression in an obese rat model - Sheldon, Ryan D. (Am J Physiol Gastrointest Liver Physiol, 2015)
The progression in nonalcoholic fatty liver disease (NAFLD) to nonalcoholic steatohepatitis is a serious health concern, but the underlying mechanisms remain unclear. We hypothesized that chronic inhibition of nitric oxide (NO) synthase (NOS) via N(ω)-nitro-l-arginine methyl ester (l-NAME) would intensify liver injury in a rat model of obesity, insulin resistance, and NAFLD. Obese Otsuka Long-Evans Tokushima fatty (OLETF) and lean Long-Evans Tokushima Otsuka (LETO) rats received control or l-NAME (65–70 mg·kg(−1)·day(−1))-containing drinking water for 4 wk. l-NAME treatment significantly (P < 0.05) reduced serum NO metabolites and food intake in both groups. Remarkably, despite no increase in body weight, l-NAME treatment increased hepatic triacylglycerol content (+40%, P < 0.05) vs. control OLETF rats. This increase was associated with impaired (P < 0.05) hepatic mitochondrial state 3 respiration. Interestingly, the opposite effect was found in LETO rats, where l-NAME increased (P < 0.05) hepatic mitochondrial state 3 respiration. In addition, l-NAME induced a shift toward proinflammatory M1 macrophage polarity, as indicated by elevated hepatic CD11c (P < 0.05) and IL-1β (P = 0.07) mRNA in OLETF rats and reduced expression of the anti-inflammatory M2 markers CD163 and CD206 (P < 0.05) in LETO rats. Markers of total macrophage content (CD68 and F4/80) mRNA were unaffected by l-NAME in either group. In conclusion, systemic NOS inhibition in the obese OLETF rats reduced hepatic mitochondrial respiration, increased hepatic triacylglycerol accumulation, and increased hepatic inflammation. These findings suggest an important role for proper NO metabolism in the hepatic adaptation to obesity.